2020
DOI: 10.3389/fonc.2020.606133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time to Castration Resistance on Cytoreductive Radiotherapy in Metastatic Castration-Resistant Prostate Cancer

Abstract: BackgroundThe role of local radiotherapy in metastatic castration-resistant prostate cancer (mCRPC) remains undefined. This study aimed to identify the value of local radiotherapy and potential candidates for mCRPC.MethodsA total of 215 patients with mCRPC treated with or without cytoreductive radiotherapy (CRT) between June 2011 and February 2019 were analyzed. Overall survival (OS) was calculated from the onset of mCRPC. The receiver-operating characteristic (ROC) curve was used to find the cutoff point for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…Furthermore, our study identified no significant correlation between the International Society of Urological Pathology (ISUP) grade at diagnosis, the duration of the hormone-sensitivity phase, the PSA level at the start of MDRT, and the subsequent progression-free survival. This observation does not align with suggestions from Mai’s cohort that patients who experience a brief hormone-sensitive phase may derive less benefit from cytoreductive radiotherapy during the castration-resistant phase of their disease [22] . However, only 28 % of patients had oligometastatic disease in this cohort.…”
Section: Discussioncontrasting
confidence: 71%
“…Furthermore, our study identified no significant correlation between the International Society of Urological Pathology (ISUP) grade at diagnosis, the duration of the hormone-sensitivity phase, the PSA level at the start of MDRT, and the subsequent progression-free survival. This observation does not align with suggestions from Mai’s cohort that patients who experience a brief hormone-sensitive phase may derive less benefit from cytoreductive radiotherapy during the castration-resistant phase of their disease [22] . However, only 28 % of patients had oligometastatic disease in this cohort.…”
Section: Discussioncontrasting
confidence: 71%
“…However, a set of tumors becomes resistant to the androgen deprivation treatment, which poses a serious therapeutic challenge 23 . These castration‐resistant prostate cancers (CRPC) exhibit high rates of metastasis and poor outcomes in the patients with PC 24,25 . They are uniquely positive for the AR but lack the sensitivity to hormone stimulation.…”
Section: Discussionmentioning
confidence: 99%